Fortification of crackers using alugbati (Basella rubra) powder. - Sevilleno, Jessica Baguio
Alugbati is one of the underutilized vegetables that can be used as a fortificant which can help address micronutrient deficiency in the country. The objective of this study is to fortify crackers using Alugbati powder. Three formulations were produced with varying concentrations of Alugbati powder (10%, 7.5% and 5%). Formulation 3 with 5% Alugbati powder was considered as the most preferred formulation. Sensory attributes and general acceptability of the most preferred formulation were assessed. Water activity, proximate composition, vitamin C and iron content were also determined and compared with the control sample. Alugabti cracker was described as light green color with moderate amount of Alugbati powder uniformly distributed throughout the cracker. The cracker is lightly crunchy and slightly salty. Alugbati odor is not perceptible while flavor of Alugbati is slightly perceptible. Alugbati cracker also obtained a general acceptability of like very much. Alugbati cracker had significantly lower water activity from 0.3268 (control) to 0.2050. Its proximate composition was composed of 3.0216% moisture content, 2.7153% ash, 12.3985% fat, 1.6862% crude fiber, 10.0352% protein and 70.1433% carbohydrate. Its vitamin C and iron content were 0.29 mg/g and 0.1569 mg/g respectively. Two sample t-test revealed a significant difference between the control sample and alugbati crackers in terms of moisture, ash, crude fat, crude fiber, protein, vitamin C and iron content. T-test also revealed that there was no significant difference between the control sample and alugbati crackers in terms of carbohydrate content. Nutritional analyses showed that vitamin C and iron content of fortified crackers increased by 64.44% and 65,54% respectively. Overall results suggest that Alugbati powder can be utilized as a potential fortificant in the production of crackers. Recommendations for further study include tests for consumer acceptability, storage stability and other nutritional composition.